How to Read Scientific Research Articles: A Hands-On Classroom Exercise. - Roxanne Bogucka; Emily Wood (Issues in Science and Technology Librarianship, 2009)
Undergraduate students are generally unfamiliar with scientific literature. Further, students experience frustration when they read research articles the way they read textbooks, from beginning to end. Using a team-based active learning exercise, an instruction librarian and colleagues at University of Texas at Austin introduce nutritional sciences students to a method for reading research papers. Librarians provide student-pairs with one section (introduction, methods, results, or discussion) of a scientific research article. Student-pairs read, discuss, and take notes, then join with pairs assigned the other sections of the article to compare their understanding of the research presented. The exercise reinforces students' critical evaluation skills by providing a productive reading strategy based on the purpose of each section of the research article. This paper describes the active learning exercise and discusses its implementation and evolution. [ABSTRACT FROM AUTHOR]